INTERAÇÃO INTERSETORIAL E A PRODUÇÃO DAS COMMODITIES AGRÍCOLAS NA REGIÃO CENTRO-OESTE: UMA ABORDAGEM ESPACIAL / INTERSETORIAL INTERACTION AND THE PRODUCTION OF AGRICULTURAL COMMODITIES IN THE BRAZILIAN CENTRAL-WEST REGION: A SPACE APPROACH: A SPACE APPROACH - Farias do Nascimento, Erianne; Justo, Wellington Ribeiro (Informe GEPEC, 2023)
Considerando a importância da agropecuária para a região Centro-Oeste, o objetivo deste trabalho é estimar o impacto da produção agropecuária, industrial e do setor de serviços na produção das culturas agrícolas da soja, do milho e do algodão herbáceo na região usando o instrumental da econometria espacial. Os resultados da Análise Exploratória dos Dados Espaciais (AEDE) mostram que há uma concentração do cultivo das três culturas na área central e no nordeste da região que refletem a formação heterogênea da agropecuária no espaço. As estimações para cada cultura revelaram que de forma geral há um efeito transbordamento significativo e cooperação entre os municípios produtores da região e um efeito positivo da agropecuária na produção das três culturas. Considering the importance of agriculture for the Brazilian Central-West region, the aim of this article is to estimate the impact the sectors of the economy in production off soybean, maize and herbaceous cotton crop production in the region on using the instruments of spatial econometrics. The results of the Exploratory Analysis of Spatial Data (EASD) show that there is a concentration of the cultivation of the three crops in the central area and in the northeast of the region that reflect the heterogeneous formation of agriculture in space. Estimates for each crop showed that in general there is a significant spillover effect and cooperation among municipalities producers in the region. There are positive effects of agricultural in production of tree crops.